2018
DOI: 10.17219/acem/73802
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of factors affecting the sense of coherence in women during pregnancy: A prospective pilot study

Abstract: Predisposing factors for the occurrence of a low rate of SOC in pregnant women are: lower age, multiparity, lack of social support, especially from the husband/partner, and the risk of depression during pregnancy. This may result from the fact that a strong SOC develops in the process of socialization, and with age we acquire the ability to accurately assess reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Engelhard et al [77] found that SOC was related positively to crisis support (particularly to con ding in others and emotional support (r = 0 .23, p = 0 .017). Similar to the ndings by Przestrzelska et al [44], Rudman et al [73] found that low SOC was associated with lack of social support using a non-validated self-report questionnaire inquiring about type and extent of social support received by a pregnant woman.…”
Section: Relationship Of Pro With Socsupporting
confidence: 66%
See 2 more Smart Citations
“…Engelhard et al [77] found that SOC was related positively to crisis support (particularly to con ding in others and emotional support (r = 0 .23, p = 0 .017). Similar to the ndings by Przestrzelska et al [44], Rudman et al [73] found that low SOC was associated with lack of social support using a non-validated self-report questionnaire inquiring about type and extent of social support received by a pregnant woman.…”
Section: Relationship Of Pro With Socsupporting
confidence: 66%
“…[34,35,37,39,46,53,56,73] did not report EPDS scores while seven studies [35,37,39,44,56,70,73] did not provide measures of SOC. Not surprisingly, none of the seven studies [35,37,39,44,56,70,73] reported relationship between EPDS and SOC measures. The study by Przestrzelska et al…”
Section: Relationship Of Pro With Socmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürde yapılan çalışmalar da gebe kadınlarda daha düşük yaş, multiparite, özellikle eş/partnerden sosyal destek eksikliği ve gebelikte depresyon riskinin düşük tutarlılık düzeyi ile ilişkili olduğunu göstermektedir. 21,22 Tutarlılık duygusu stresli olayların deneyimini azaltan kişisel bir kaynaktır. 23 Gelir durumu yüksek olan ve isteyerek gebe kalan kadınların hayatlarında kriz yaratabilecek daha az stres kaynağı ile karşılaştığı ve bu nedenle yüksek tutarlılığa sahip olduğu düşünülmektedir.…”
Section: Discussionunclassified
“…27 Özellikle eşten görülen sosyal destek tutarlılık duygusunu da olumlu etkilemektedir. 28 Literatür ve çalışmamızdan elde edilen veriler kadınların prenatal bağlanma düzeyi ile eğitim durumu, sosyoekonomik düzeyi ve sosyal destek görme durumu arasında ilişki olduğunu göstermektedir. Doğum öncesi dönemde kurulan güçlü ve sağlıklı bir bağlanma, doğum sonrası dönemde anne-bebek bağlanma sürecine olumlu katkı sağlamaktadır.…”
Section: İstatistiksel Analiz Yöntemleriunclassified